Meta-Analisis pengaruh faktor daya dukung etiologi sirosis terhadap keberhasilan curcumin sebagai terapi - Winnie Nirmala Santosa; Dwi Martha Nur Aditya (Universitas Jenderal Achmad Yani Yogyakarta, 2022)
Background: Cirrhosis is a liver disease that affects 20-30% of people in Indonesia. The etiologic of cirrhosis include autoimmune, hepatitis B, portal vein thrombosis, and alcoholism. The existence of etiological factors may but has not been proven to, influence the success of curcumin therapy.Objective: This meta-analysis examines the research to show how etiological variables might affect cirrhotic patients' response to curcumin treatment.Methods: The searching terms